Diversity of Mollusks (Gastropods and Bivalves) in The Bagek Kembar Mangrove Ecosystem Essential Area, Sekotong - Handrayani, Handrayani; Idrus, Agil Al; Jamaluddin, Jamaluddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Bagek Kembar Mangrove Ecosystem Essential Area (EEA) in West Lombok is a critical habitat that supports various aquatic organisms, including mollusks. This study aimed to identify and analyze the diversity of mollusks from the classes Gastropoda and Bivalvia, within the Bagek Kembar mangrove ecosystem. Sampling was conducted from February to April 2025 using the quadrat transect method, and data were analyzed using the Shannon-Wiener diversity index (H′), Pielou’s evenness index (E), and Simpson’s dominance index (C). A total of 2,368 individual mollusks were recorded, comprising 20 species: 16 Gastropods and 4 Bivalves. The family Potamididae from the class Gastropoda was the most dominant, with Cerithidea cingulata being the most abundant species. Gastropods exhibited moderate diversity (H′ = 2.20), high evenness (E = 0.79), and low dominance (C = 0.15), while Bivalves showed low diversity (H′ = 0.61), moderate evenness (E = 0.44), and moderate dominance (C = 0.70). These results indicate that mollusk diversity in the area is at a moderate level. The findings highlight the importance of mangrove ecosystems in maintaining mollusk diversity and support their use as bioindicators in environmental monitoring and local conservation strategies.